Sirolimus for progressive neurofibromatosis type 1–associated plexiform neurofibromas: a Neurofibromatosis Clinical Trials Consortium phase II study - Weiss, Brian (Neuro Oncol, 2015)
BACKGROUND: Plexiform neurofibromas (PNs) are benign peripheral nerve sheath tumors that arise in one-third of individuals with neurofibromatosis type 1 (NF1). They may cause significant disfigurement, compression of vital structures, neurologic dysfunction, and/or pain. Currently, the only effective management strategy is surgical resection. Converging evidence has demonstrated that the NF1 tumor suppressor protein, neurofibromin, negatively regulates activity in the mammalian Target of Rapamycin pathway. METHODS: We employed a 2-strata clinical trial design. Stratum 1 included subjects with inoperable, NF1-associated progressive PN and sought to determine whether sirolimus safely and tolerably increases time to progression (TTP). Volumetric MRI analysis conducted at regular intervals was used to determine TTP relative to baseline imaging. RESULTS: The estimated median TTP of subjects receiving sirolimus was 15.4 months (95% CI: 14.3–23.7 mo), which was significantly longer than 11.9 months (P < .001), the median TTP of the placebo arm of a previous PN clinical trial with similar eligibility criteria. CONCLUSIONS: This study demonstrated that sirolimus prolongs TTP by almost 4 months in patients with NF1-associated progressive PN. Although the improvement in TTP is modest, given the lack of significant or frequent toxicity and the availability of few other treatment options, the use of sirolimus to slow the growth of progressive PN could be considered in select patients.